BENCANA INTOLERANSI ANTARUMAT BERAGAMA DALAM RUANG PUBLIK INDONESIA - Yohanes Daga (Aggiornamento, 2021)
The author focused on the subject of inter-religious tolerance in Indonesia. This theme was proposed as a criticism of unequal practices in the name of a particular religion. Religious pluralism in Indonesia describes the Indonesian nation as a diverse nation. Essentially, all religions teach truth, peace, and create unity. Its realization is very important for the realization of interfaith tolerance. However, due to the emergence of various problems that threaten the integrity of the country, unity and tolerance are gradually disappearing. Religious pluralism is no longer seen as a treasure that must be preserved, but an enemy that must be destroyed. With signs of the country’s disintegration, this issue has become more and more complex. To explore this topic, the author uses a critical reading method. The author collected information from various books, periodicals, the Internet, and newspapers. Indonesia's discourse on inter-religious conflicts has never been completely resolved. The concept of tolerance is still difficult to realize. The author believes that tolerance is a relationship. To establish unity, there is a cooperative relationship among them.